Photonic crystals band diagrams computation by using extreme learning machine - Da Silva Ferreira, Adriano; Malheiros-Silveira, Gilliard Nardel [UNESP]; Hernandez-Figueroa, Hugo Enrique (Optica Publishing Group, 2018)
We modeled Extreme Learning Machine feed-forward artificial neural network for estimating band diagrams of tri-dimensional photonic crystals and demonstrated a simple approach for speedy computations.